Brazilian Multinationals ́ Competences: Impacts of a “Tug of War” Between Cultural Legacies and Global Mindedness - Germano Glufke Reis; Maria Tereza Leme Fleury; Afonso Carlos Corrêa Fleury; Felipe Zambaldi (BBR: Brazilian Business Review)
This study investigates the simultaneous influences of culture and global mindedness on the foreign subsidiaries of Brazilian multinationals (B rMNs). Because the ability to develop competences abroad is critical for emerging multina tionals competitiveness, we proposed hypotheses and tested a model for how the competenc es of subsidiaries may be affected by the dimensions of global mindedness and culture. To do so, we conducted a multilevel survey involving the headquarters and subsidiaries of majo r BrMNs. The results suggest that global mindedness, which encompasses global orientation, g lobal knowledge, and global skills, is positively related to the development of subsidiari es ́ competences. By contrast, cultural factors, including power distance and uncertainty a voidance, are negatively related to competences development. Therefore, these dimension s may exert simultaneous and opposing stimuli and unaligned forces that affect the develo pment of competences abroad, generating a “tug of war” effect.